L’INFLUENCE DE L’INTERACTION EDUCATIVE DE LA CLASSE X À SMAN 2 MAGELANG SUR L’INTERET D’APPRENDRE LE FRANÇAIS - Astuti, Putri Dwi; Sudarwoto, Sudarwoto; Handayani, Sri (Didacticofrancia: Journal Didactique du FLE, 2019)
L?interaction éducative est une interaction entre le professeur et les lycéens dans l?apprentissage. La bonne interaction donne la motivation aux lycéens, alors ils ont l?intérêt à apprendre les matières. L?objectif majeur de cette recherche est de décrire l?influence de l?interaction éducative à l?intérêt à apprendre le français.  C?est une recherché corrélationnelle dont les variables sont l?interaction éducative et l?intérêt à apprendre le français. La population est les lycéens de la classe X au SMA N 2 Magelang. J?ai utilisé l?enquête pour collecter les données d?interaction éducative et l?intérêt à apprendre du français. Cette recherche a utilisé la validité construque et pour savoir la réalibilité d?enquête, j?ai utilisé la formule d?Alpha. J?ai utilisé la formule de Product-moment pour analyser les donneés. Le résultat du Product moment est rxy = 0,965, rtable = 0,297. Cela montre qu?il y a une influence de l?interaction éducative à l?intérêt à apprendre le français. The interaction between teacher and students in the learning process called educative interaction. The good interaction can give the motivation toward students so it will create interest in the learning process. The research problem are the influence of the interaction toward students? learning interest in French for grade X in SMA N 2 Magelang. The aim of this research is to describe the influence of educative interaction toward students? learning interest in French for grade X in SMA N 2 Magelang. This research is correlational research. The variable are educative interaction, and students? learning interest. The population of this research is the students of grade X, SMA N 2 Magelang. Questionnaire were used to collect the data about educative interaction and learning interest of French. This research use construct validity and alpha formula to measure the reliability of the questionnaire. The collective data were analyzed with product moment correlation formula. The result of the product moment is rhitung = 0,965, rtabel = 0,297. It can be concluded that there is an influence of educative interaction toward students? learning interest in French of grade X SMA N 2 Magelang.